2018
DOI: 10.1108/jbim-04-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

Fairness in franchisor–franchisee relationship: an integrative perspective

Abstract: Purpose This paper aims to elucidate and extend the concept of power and fairness in the context of franchisor–franchisee relationship. Design/methodology/approach On the basis of Dul and Hak’s (2007) recommendations, the conceptual model is developed from closely related domains (e.g. channel relationship) using pertinent theories. On the basis of this comprehensive analysis, new propositions about fairness in a franchisee–franchisor context are drawn. The primary purpose of this research is to conceptually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 107 publications
1
23
0
Order By: Relevance
“…The results of our empirical research are in line with Kim et al (2017), who also concluded that fairness contributes to the innovation performance of supplier-buyer partnerships. Additionally, we were able to confirm the conclusions of Shaikh et al (2018), showing that suppliers who perceive the partnership to be fair are less likely to be opportunistic. This study, therefore, alerts managers to refrain from cannibalizing the partnership’s pie-sharing for realizing an immediate financial surplus at their partner’s expense, as it harms both the partnerships and the firm’s own lasting performance.…”
Section: Discussionsupporting
confidence: 57%
“…The results of our empirical research are in line with Kim et al (2017), who also concluded that fairness contributes to the innovation performance of supplier-buyer partnerships. Additionally, we were able to confirm the conclusions of Shaikh et al (2018), showing that suppliers who perceive the partnership to be fair are less likely to be opportunistic. This study, therefore, alerts managers to refrain from cannibalizing the partnership’s pie-sharing for realizing an immediate financial surplus at their partner’s expense, as it harms both the partnerships and the firm’s own lasting performance.…”
Section: Discussionsupporting
confidence: 57%
“…franchisors). Previous research has demonstrated that franchisor – franchisee relationship quality is an important driver of franchise growth (Shaikh et al , 2018). Therefore, it can be suggested that an effective EE program has a positive impact on the franchise performance through its influence on the EE participants i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The EE intervention was focused on the behavioural outcomes of “would-be” entrepreneurs including their decision-making competencies in recognising and evaluating opportunities to enter franchising as franchisees and to operate their business successfully. Although franchising offers individuals a business model that involves reduced risk, high rates of conflict are still evident within many franchise sectors around the world (Bordonaba-Juste et al , 2011; Frazer et al , 2014; Perry et al , 2002; Shaikh et al , 2018). Indeed, problems associated with incomplete information, lack of business acumen and inadequate due diligence during the pre-entry decision making stage have been said to foster the creation of unrealistic expectations (regarding future performance of the franchise unit), manifesting in negative behavioural outcomes such as dissatisfaction and conflict (Giddings et al , 2010; Weaven et al , 2010).…”
Section: Pre-intervention: Development and Implementationmentioning
confidence: 99%
“…Power, in general terms, refers to the ability of an entity to influence the action of another entity (Chicksand, 2015; Shamdasani et al , 2001). In any business relationship, power plays an important role in the growth of channel leader and members (Shaikh et al , 2018). The synchronization of goals between channel members is very crucial for realizing the growth potential (Sadarangani, 2013; Jain et al , 2014).…”
Section: Introductionmentioning
confidence: 99%